Relationship Between Vaginal Hygiene Behavior and Levels Stress With Leukorrhea Incidence on Young Women at School - Nur Suci Ainniyah Thayib; Zuhriana K. Yusuf; Siti Hajar Salawali (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Leukorrhea (vaginal discharge) is a reproductive health problem that is often experienced by adolescent girls. The incidence of leukorrhea can be influenced by vaginal hygiene behavior and stress levels. Improper vaginal hygiene behavior and stress can lead to imbalances in the normal flora of the vagina and hormonal changes that trigger the occurrence of leukorrhea. This study analyzes the relationship between vaginal hygiene behavior and stress levels with the incidence of leukorrhea in adolescent girls at Madrasah Aliyah Negeri 1 Gorontalo City. It was conducted with a cross-sectional observational analytical design of 275 respondents selected through proportionate stratified random sampling from a population of 884 adolescent girls. Primary data were collected via validated questionnaires (Cronbach's alpha >0.6 for vaginal hygiene and leukorrhea, DASS-42 for stress), analyzed univariate (frequency) and bivariate (Spearman rank test, ?=0.05). The results showed that the majority of respondents were 16 years old (37.8%), class X (35.6%), adequate vaginal hygiene behavior (76.4%), moderate stress (62.5%), and normal leukorrhea (76%). There was a significant relationship: vaginal hygiene behavior with leukorrhea (r=-0.155, p=0.010, weak negative), and stress level with leukorrhea (r=0.517, p=0.000, moderate positive). Conclusion: Good hygiene behaviors lower the risk of leukorrhea, while high stress increases it; Reproductive Health Education Advice in Schools for Prevention